La dynamique des indicateurs de santé sur la population de Roumanie dans le contexte européen - MIRELA VASILICA DOBRIN (Cinq Continents, 2012)
Dynamics of the Romanian population health indicators in the european context. This article aims to analyze the evolution of the most important health indicators to highlight the situation of the Romanian population in terms of health. Romanian population's health will be analyzed and a European comparative perspective, emphasizing Romania's position in relation to other European countries. Will be used as indicators: life expectancy, general mortality, infant mortality and the number of cases of illness. Progress will be monitored the health of the population of Romania between 1990-2008, using statistical data and data from various national and European research. Article is based on the use of multiple data sources: Diagnosis Quality of Life 1990-2006, NSI, Eurostat.